Oil and Human Capital: Rethinking about Resource Curse Hypothesis in Iran - Younes Nademi; Hoda Zobeiri (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2017)
Human capital is one of the most important inputs in production function that this factor has a crucial role in economic development process. Human capital in oil-dependent countries such as Iran could be affected by oil revenues as well as the form of distribution of oil rent. These evidences accompanied with contradictory and ambiguous impacts. The aim of this paper is to investigate the nonlinear impact of oil revenue on human capital in Iran during the period of 1975-2014. For this purpose, by using a threshold regression model, human capital has been modeled. The empirical results indicate that when the share of oil revenues in GDP is less than about 0.09, increasing share of oil revenues in GDP has a positive significant impact on human capital that the estimated coefficient is 20.21. But after the threshold level, increasing the share of oil revenue in GDP has a significant positive impact on human capital that the estimated coefficient is 5.37. Therefore, the intensity of oil revenue effect on human capital has been dramatically decreased in high oil revenue regime rather than the low oil revenue regime. Therefore, decreasing dependency to oil revenues increases human capital.